Development of high-performance oxygen evolution reaction electrocatalyst with quick kinetics: Based on ultrafine Cu nanoparticles encircled by N-doped carbon. (April 2023) - Waheed, Muhammad Suleman; Aman, Salma; Gouadria, Soumaya; Alsaiari, Norah Salem; Manzoor, Sumaira; Zubar, T.I.; Tishkevich, Daria I.; Trukhanov, Sergei V.; Al-Buriahi, M.S.; Trukhanov, Alex V.
Abstract: The oxygen evolution reactions (OER) in electrochemical water splitting are the chief catalytic processes to clean and sustainable energy technologies, such as water electrolysis or energy conversion system. This study presents a Mott-Schottky catalyst encircled copper nanoparticles, including the nitrogen doped carbon layers (Cu@NC). All the fabricated materials are analyzed via numerous complementary procedures and then employed under a potentiostat configured with a three-electrode system. The fabricated Cu@NC displays a lower overpotential of 101.0 mV to accomplish current density of 10.0 mA cm −2, lower Tafel slope of 42.0 mV dec −1, and extensive stability over 5000 cycles having exceptional oxygen evolution activity. The structural results reveal that adding Cu and N species in Cu@NC significantly enhances the numerous of active sites and improves electronic conductivity. Structural defects help to accelerate the oxygen evolution process and many other fields for future applications. Highlights: Cu nanoparticles entrapped between the graphitic carbon nanosheet. The chronoamperometry and cycling stability of Cu@NC. N-doped graphene porous nanosheet speeds up the OER reaction kinetics. Adsorption of byproducts on the external surface of the active catalyst.